HGG-40. HIGH GRADE GLIOMA CELL LINE COHORT AS AN EXAMPLE OF CHILDREN'S BRAIN TUMOR TISSUE CONSORTIUM TUMOR SPECIMEN PROCESSING PIPELINE. Issue 2 (22nd June 2018) - Koptyra, Mateusz; Baubet, Valerie; Tauhid, Lamiya; Choudhari, Namrata; Smith, Tiffany; Cole, Kristina; Ijaz, Heba; Waanders, Angela; Resnick, Adam
Abstract: The Children's Brain Tumor Tissue Consortium (CBTTC) is a multi-institutional collaborative research program dedicated to accelerating pediatric brain tumor research. Tumor specimens collected by CBTTC undergo multidimensional tumor analysis including genomic, transcriptomic and proteomic data generation, providing freely available data for researchers worldwide. Moreover, CBTTC advances pediatric research efforts by generating cell lines and and patient-derived xenografts (PDX) providing these freely available materials for researchers worldwide. High-grade gliomas (HGG) in children is the most prevalent among brain tumors with a dismal prognosis. Preclinical testing has been limited due to lack of pediatric specific HGG in vitro and in vivo models. Here we present a cohort of pediatric HGG cell lines developed within the CBTTC. The cells were derived from 10 subjects from fresh or frozen tumor tissues and generated in different culture conditions. Results include the cells' basic molecular characteristics and tumor formation in vivo, which presents valuable information for preclinical studies. We also report how our cell culture conditions affect the morphology, growth and genetic makeup of developed tumor cell lines. These results can intersect with tumor molecular profiling to provide a transparent view of cell line utility for cell biology and drug development studies. This project serves as an example of CBTTC's pipeline for cell line development, and brings important insights for the processes of brain tumor specimen derived tool generation.